Middle-Century Islamic Literature: (Relations and Networks Between Islamic Libraries in the Context of Islamic Daulas) - Isna Fistiyanti; Rina Juni Rianty; Aden Hudiana (JPUA: Jurnal Perpustakaan Universitas Airlangga: Media Informasi dan Komunikasi Kepustakawanan, 2022)
A B S T R A C T The research aims to find out the history of literature in the Umayyad era, the Abbasid era, and find out how the relationship between this Islamic library network is. The method used in this study is to use historical research methods. Historical research also has stages of research methods. The first is finding the topic first, the next is the heuristic stage which means finding and gathering sources to be able to find out all past historical events or events, and the next stage is interpretation. The conclusion of this study is that during the Umayyad Daula period a breakthrough was made by developing private libraries, but also developing public libraries. Not a few from this era there are figures who are writers or authors of works in certain fields. Meanwhile, during the Abbasid period, it became the pinnacle of Islamic civilization. Muslim scholars who were experts in various sciences, both religious and non-religious, also appeared at this time. The development of civilization that was so rapid was also supported by the economic progress of the empire which became a link between the eastern and western worlds. Relatively good political stability, especially during the early Abbasid period, also became a trigger for the progress of Islamic civilization. Scientific relations in relation to Islamic literature is a complex relationship. From a historical point of view, this relationship has been established between the West and the East and vice versa, long before the appearance of Islam in the Arabian Peninsula, when the influence of Hellenism had spread to the eastern regions of Persia, Alexandria, Iraq. Keywords: Islamic Literature; Abbasid Daula; Umayyad Daula A B S T R A K Penelitian ini berusaha memahami hubungan antara jaringan perpustakaan Islam ini dengan sejarah sastra pada masa Bani Umayyah dan Abbasiyah. Pendekatan yang dilakukan dalam karya ini adalah dengan melakukan penelitian sejarah. Tahapan metodologi penelitian sering digunakan dalam studi sejarah. Menemukan topik didahulukan, kemudian muncul langkah heuristik, yaitu menemukan dan mengumpulkan informasi untuk mempelajari semua peristiwa atau peristiwa sejarah sebelumnya, dan terakhir adalah tahap interpretasi. Kesimpulan penelitian ini adalah bahwa periode Daulah Umayyah mengalami terobosan dalam perkembangan perpustakaan baik swasta maupun umum. Ada beberapa orang dari era ini yang merupakan sastrawan atau penulis karya dalam bidang tertentu. Sementara itu terjadi, ia naik ke puncak budaya Islam selama era Abbasiyah. Pada masa ini, para ilmuwan Muslim dengan keahlian di berbagai bidang—baik agama maupun sekuler—juga mulai bermunculan. Pertumbuhan ekonomi kekaisaran, yang berfungsi sebagai jembatan antara dunia timur dan barat, berkontribusi pada perkembangan peradaban yang cepat. Stabilitas politik yang umumnya kondusif, khususnya pada periode awal Abbasiyah, menjadi katalis bagi kemajuan peradaban Islam. Ada hubungan yang rumit antara sains dan sastra Islam. Dari segi sejarah, interaksi antara Barat dan Timur dan sebaliknya ini sudah terbentuk jauh sebelum masuknya Islam di Jazirah Arab, ketika Hellenisme sudah menjangkiti wilayah timur Persia, Aleksandria, dan Irak. Kata Kunci: Kepustakaan Islam; Daulah Abbasiyah; Daulah Ummayyah.